Regulatory T Cells in Autoimmune Hepatitis: Unveiling Their Roles in Mouse Models and Patients - Wang, Han; Feng, Xinxia; Yan, Wei; Tian, Dean (Frontiers in Immunology, 2020)
Autoimmune hepatitis (AIH) is a severe and chronic liver disease, and its incidence has increased worldwide in recent years. Research into the pathogenesis of AIH remains limited largely owing to the lack of suitable mouse models. The concanavalin A (ConA) mouse model is a typical and well-established model used to investigate T cell-dependent liver injury. However, ConA-induced hepatitis is acute and usually disappears after 48 h; thus, it does not mimic the pathogenesis of AIH in the human body. Several studies have explored various AIH mouse models, but as yet there is no widely accepted and valid mouse model for AIH. Immunosuppression is the standard clinical therapy for AIH, but patient side effects and recurrence limit its use. Regulatory T cells (Tregs) play critical roles in the maintenance of immune homeostasis and in the prevention of autoimmune diseases, which may provide a potential therapeutic target for AIH therapy. However, the role of Tregs in AIH has not yet been clarified, partly because of difficulties in diagnosing AIH and in collecting patient samples. In this review, we discuss the studies related to Treg in various AIH mouse models and patients with AIH and provide some novel insights for this research area.